Hypothyroidism and Hyponatremia: Simple Association or True Causation - Ahmet Bahadir Ergin; James Bena; Christian E Nasr (Open Journal of Thyroid Research - Peertechz Publications, 2017)
Background: Hypothyroidism has been classically considered as a cause of hyponatremia. This causality has been controversial in clinical practice. The purpose of this study was to reexamine the association between thyroid state and serum sodium concentration in a large cohort of subjects Methods: This was a chart review using electronic health records. The prevalence of the coexistence of hyponatremia and hypothyroidism as well as the magnitude of the correlation were investigated. All patients who were seen between September 1, 2005 and August 31, 2007 in Cleveland Clinic hospitals and out-patient clinics who had serum sodium and TSH. Main Outcome Measure was correlation between serum Na and TSH. Results: There were 143,720 unique patients. A very small negative correlation was found between increasing TSH and blood sodium levels (r: -0.01, p<0.001, 95% CI (-0.02,-0.01)). All the patients who had hyponatremia in the setting of elevated TSH had 2 or more other factors known to cause hyponatremia.